CEDAW: Compliance and Contestation in Latin America - Shirley, Sheryl L. (European Scientific Journal, ESJ, 2016)
Integrating legal history and social science method of analysis is helpful for understanding women’s human rights in comparative context. This study examines the roles of Latin American states in the development of CEDAW, the international treaty on women’s rights. By then reviewing reports on Peruvian and Chilean compliance with CEDAW, the study begins to assess whether the international women’s convention has relevance for non-governmental organizations (NGOs) and practitioners who seek to promote women’s rights. At the state level, women’s human rights are neither imposed by the CEDAW Committee nor are rights simply constructed locally within the confines of isolated states. In-depth analysis of Peru’s and Chile’s recent compliance efforts suggests policymakers and activists have used CEDAW as a tool to push for more equitable legal, institutional, and social reforms.